Pengembangan LKPD Berbasis Etnomatematika Pada Alat Musik Tradisional Minangkabau Untuk Memaksimalkan Hasil Belajar Siswa - Winda Maysa Istiqomah; Isnaniah Isnaniah; Junaedi Junaedi; M. Imamuddin (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
Research This research is motivated by the problems found in class IX Integrated MTsS Guguak Randah is that the LKPD used by educators is not yet culturally based, based on the national education system, educators should facilitate learning for students with local culture. Based on the information information obtained, the learning outcomes of students are relatively low, because there are still. Based on the information obtained, the learning outcomes of students are low, because there are still many students below the KKM set at school, namely 75. develop learning materials to help students in construct mathematical knowledge easily and interestingly. One of the teaching materials developed is the Ethnomathematics-Based Learner Worksheet (LKPD). Ethnomathematics on Minangkabau Traditional Musical Instruments. This research aims to produce Ethnomathematics-based LKPD on Minangkabau Traditional Musical Instruments in class IX MTsS Integrated Guguak Randah which meet the criteria of valid, practical and effective. This research is a Research and Development (R&D) with the ADDIE development model. The validity test is seen from a validation sheet consisting of six validators, namely material experts, educational technology experts, linguists and experts. validators, namely material experts, educational technology experts, linguists and cultural experts. then improved according to the validator's suggestions. Practicality test seen from the learner response questionnaire and the effectiveness test seen from the learning outcomes of students in the form of tests. learning outcomes in the form of tests. Data analysis techniques used to express the results of this study are 1) Validity Data Analysis, 2) Practicality Analysis, and 3) Effectiveness Analysis. Based on the development research that has been done based on the development research that has been carried out, the LKPD is obtained with a validity level of 83.48% which is very valid, for a practicality level of 87.38% which is very practical, and for an effectiveness level. is on very practical criteria, and for the effectiveness level 75% is on effective criteria. in the effective criteria. It can be concluded that the Ethnomathematics-Based LKPD on Minangkabau Traditional Musical Instruments in Class IX Integrated MTsS Guguak Randah which was developed met the valid, practical and effective criteria. developed meets the criteria of valid, practical and effective.